Analisis Mashlahah Terhadap Putusan Mahkamah Konstitusi Nomor 22/PUU-XV/2017 - Wiwin, Wiwin (Jurnal Litigasi Amsir, 2023)
This article discusses the Constitutional Court’s Decision No. 22/PUU-XV/2017 which equalizes the age limit for marriage in Indonesia. The article employs a normative legal research method with a focus on legislation, analytical, conceptual, and maslahah approaches. The research findings indicate that Constitutional Court Decision No. 22/PUU-XV/2017 is based on philosophical, juridical, and sociological considerations, emphasizing the importance of equal age limits for marriage in Indonesia. Consequently, the phrase "age 16" in Article 7, Paragraph (1) of Law No. 1 of 1974 concerning Marriage is deemed inconsistent with the 1945 Constitution. The equalization of age limits for marriage in Constitutional Court Decision No. 22/PUU-XV/2017 encompasses aspects of maslahah, such as protecting the rights of women who have been marginalized due to differing age limits for marriage between men and women. Moreover, Constitutional Court Decision No. 22/PUU-XV/2017 also promotes the maslahah of gender equality in the legal regulation of marriage in Indonesia.